Patient-family agreement on values and preferences for life-sustaining treatment: results of a multicentre observational study. Issue 1 (22nd July 2017) - Abdul-Razzak, Amane; Heyland, Daren K; Simon, Jessica; Ghosh, Sunita; Day, Andrew G; You, John J
Abstract : Objectives: To quantify agreement between patients and their family members on their own values and preferences for use or non-use of life-sustaining treatments for the patient. Methods: Hospitalised patients aged 55 years or older with advanced pulmonary, cardiac, liver disease or metastatic cancer or aged 80 years or older from medical wards at 16 Canadian hospitals and their family members completed a questionnaire including eight items about values related to life-sustaining treatment and a question about preferences for life-sustaining treatments. Results: We recruited a total of 313 patient-family member dyads. Crude agreement between patients and family members about values related to life-sustaining treatment was 42% across all eight items but varied widely: 20% when asking how important it was for the patient to respect the wishes of family members regarding their care; 72% when asking how important it was for the patient to be kept comfortable and suffer as little as possible. Crude agreement on preferences for life-sustaining treatment was 91% (kappa 0.60; 95%CI 0.45 to 0.75) when looking at preferences for cardiopulmonary resuscitation (CPR) versus no CPR but fell to 56% when including all five response options with varying degrees of resuscitative, medical or comfort options (kappa 0.39; 95%CI 0.31 to 0.47). Conclusions: There is appreciable disagreement between seriously ill hospitalised patients and family members in their values and preferences for life-sustaining treatment. Strategies are needed to improve the quality of advance care planning, so that surrogates are better able to honour patient's wishes at the end of life.